A review of first-in-human small molecule oncology clinical trials - Greenwood, Daniel; Stratford, Ian; Booth, Steven (International Journal of Clinical Trials, 2016)
First-in-human (FIH) oncology clinical trials are crucial to the development of small-molecule oncology candidates. However, there is a dearth of research investigating how these trials vary from one-another and therefore whether one approach may be better than another. This review aims to investigate variation of FIH trials published over the last decade with respect to four areas: publication particulars; trial design; patient particulars and drug administration and formulation.